2018
DOI: 10.1111/jth.13964
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase B2 and N play different roles in regulation of activated complements C3a and C5a in mice

Abstract: Background There are two basic carboxypeptidases in plasma. Carboxypeptidase B2 (CPB2) is activated from a circulating zymogen, proCPB2, and carboxypeptidase N (CPN) is constitutively active with both inactivating complement C3a and C5a. Aims To test the roles of CPB2 and CPN in complement-driven mouse models of cobra venom factor (CVF) challenge and hemolytic-uremic syndrome (HUS). Methods Cpb2 , Cpn and wild-type (WT) mice were compared in an HUS model induced by Shiga toxin and lipopolysaccharide administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…The CPB2 generated will then be able to inactivate C3a and C5a. This hypothesis is in agreement with the data from the HUS model, in which deficiency of CPB2 has a greater effect than deficiency of CPN . In humans, the importance of CPB2 in regulating C5a is shown by the association of the long‐acting CPB2 form with a reduced risk of developing severe rheumatoid arthritis .…”
Section: Different Roles Of Cpb2 and Cpnsupporting
confidence: 89%
See 3 more Smart Citations
“…The CPB2 generated will then be able to inactivate C3a and C5a. This hypothesis is in agreement with the data from the HUS model, in which deficiency of CPB2 has a greater effect than deficiency of CPN . In humans, the importance of CPB2 in regulating C5a is shown by the association of the long‐acting CPB2 form with a reduced risk of developing severe rheumatoid arthritis .…”
Section: Different Roles Of Cpb2 and Cpnsupporting
confidence: 89%
“…No phenotype has been observed in these animals without a challenge, suggesting that there is no requirement for any plasma basic carboxypeptidase during reproduction and development. When challenged with CVF, 50% of the Cpb2 À/À /Cpn À/ À mice died, in comparison with complete survival of Cpb2 À/À , Cpn À/À and WT mice [52]. Thirty minutes after administration of CVF, the clinical health score showed that WT mice were unaffected, that there was little effect on Cpb2 À/À mice, and that Cpn À/À mice were almost as badly affected as Cpb2 À/À /Cpn À/À mice.…”
Section: Disease Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…The work of Morser et al . described in this issue of JTH is a major step forwards in that direction.…”
mentioning
confidence: 99%